Nickel-based catalyst, preparation method and application thereof, and method for synthesizing ammonia
By optimizing the formulation and preparation process of nickel-based catalysts, the catalytic activity is improved by using additive metals, which solves the problem of insufficient activity of nickel-based catalysts under low temperature and low pressure conditions, and realizes a highly efficient synthesis of ammonia.
Patent Information
- Application Number
- CN202411873166.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-21
AI Technical Summary
The lack of catalytic activity of nickel-based catalysts under low temperature and low pressure conditions limits their wide application in ammonia synthesis process.
An alloy containing Ni, Al and additive metal is used for catalyst preparation, and an efficient nickel-based catalyst is formed through steps such as grinding, dealuminizing and aging. The additive metal is selected from the group VA metal, transition metal and lanthanide metal, preferably Ru, Mo, Re, La, Sb, Bi, and Ag, and the additive metal content accounts for 0.1-5 wt% of Ni.
It realizes efficient catalytic synthesis of ammonia under low temperature and low pressure conditions, reduces energy consumption and equipment requirements, and provides an economical, efficient and safe synthesis of ammonia.
Smart Images

Figure CN119657159A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of catalyst preparation, and in particular to a nickel-based catalyst and a preparation method and application thereof, as well as a method for synthesizing ammonia. Background Art
[0002] As one of the core reactions in the chemical industry, synthetic ammonia is of great importance. From nitrogen fertilizer production in the agricultural field, to drug synthesis in the medical field, to hydrogen energy development in the energy field, synthetic ammonia plays a pivotal role. However, for a long time, the traditional synthetic ammonia process has been limited by high temperature and high pressure conditions. This not only means huge energy consumption, but also puts extremely high demands on production equipment, making the investment cost of the entire production process high.
[0003] In recent years, with the increasing attention paid to sustainable development and green chemistry around the world, the ammonia synthesis process has also ushered in a wave of technological innovation. In particular, low-temperature and low-pressure ammonia synthesis technology has become a hot topic of research in the chemical industry because it can significantly reduce energy consumption and reduce equipment requirements. For example, patent application CN117920204A discloses a Ru / SrTiO3 catalyst. The application adjusts the oxygen vacancies and electronic states by adding alkali metals or alkaline earth metals to the catalyst, so that the catalyst exhibits extremely high catalytic ammonia synthesis activity and stability at low temperature and low pressure, and can effectively inhibit the hydrogen poisoning effect that occurs in traditional carriers. CN114471552B discloses a method and device for the coordinated synthesis of ammonia by plasma thermal catalysis of water vapor and nitrogen, which achieves 15176 μmol·g under the action of Ru / PrCeO3. -1 ·h -1 NH3 yield. In low-temperature and low-pressure ammonia synthesis technology, the relatively expensive precious metal Ru is generally used as the active component, which greatly increases the manufacturing cost of the catalyst. Nickel-based catalysts not only have a wide range of applicability and can show excellent catalytic performance under a variety of reaction conditions, but also their high efficiency and economy make them an ideal choice for ammonia synthesis reactions.
[0004] However, the catalytic activity of nickel-based catalysts under low temperature and low pressure conditions is a key factor restricting their widespread application. Therefore, how to further improve the performance of nickel-based catalysts under low temperature and low pressure conditions has become an urgent problem to be solved in the current research on synthetic ammonia technology. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems of high cost and harsh reaction conditions of ammonia synthesis catalysts in the prior art, and to provide a nickel-based catalyst and a preparation method and application thereof, as well as a method for synthesizing ammonia. The nickel-based catalyst can catalyze nitrogen and hydrogen to synthesize ammonia under mild conditions of low temperature and low pressure.
[0006] In order to achieve the above object, the present invention provides a method for preparing a nickel-based catalyst in a first aspect, the method comprising the following steps: (1) providing an alloy containing Ni, Al and an additive metal, wherein the additive metal is selected from at least one of Group VA metal elements, transition metal elements other than Group IVB and Group VB, and lanthanide metal elements; (2) grinding the alloy to obtain alloy powder; (3) subjecting the alloy powder to dealuminizing treatment in the presence of an alkali solution; (4) Aging the product obtained by the dealumination treatment in step (3) and the catalyst support in the presence of a solvent.
[0007] According to the present invention, preferably, the auxiliary metal is selected from at least one of Co, Cu, Ag, Ru, Mo, Re, La, Sb and Bi, preferably Ru, Mo, Re, La, Sb, Bi, Ag, and more preferably Ru and / or Mo.
[0008] According to the present invention, preferably, the additive metal content accounts for 0.1-5wt% of the Ni metal content, preferably 1-3wt%.
[0009] According to the present invention, preferably, in step (1), the mass ratio of Ni to Al is 1:(1-3), preferably 1:(1-2).
[0010] The second aspect of the present invention provides a nickel-based catalyst prepared by the preparation method described in the first aspect.
[0011] The third aspect of the present invention provides use of the nickel-based catalyst of the second aspect in synthesizing ammonia.
[0012] A fourth aspect of the present invention provides a method for synthesizing ammonia, comprising: contacting nitrogen and hydrogen under ammonia synthesis conditions in the presence of a nickel-based catalyst and a solvent; wherein the nickel-based catalyst is the nickel-based catalyst described in the second aspect above.
[0013] Through the above technical solution, the nickel-based catalyst provided by the present invention, its preparation method and application, and the method for synthesizing ammonia achieve the following beneficial effects: (1) The present invention uses non-precious metal Ni as the main active component of the catalyst, successfully replacing the traditional low-pressure ammonia synthesis Ru metal, and provides a direction for the development of low-cost ammonia synthesis catalysts.
[0014] (2) The present invention achieves efficient catalytic synthesis of ammonia at low temperature and low pressure by optimizing the catalyst formula and reaction route, solving the problem of overly harsh reaction conditions for traditional ammonia synthesis, greatly reducing the energy consumption and equipment requirements for the reaction, and providing a more economical, efficient and safe solution for the synthetic ammonia industry.
[0015] (3) The fully mixed flow reaction mode preferably adopted in the present invention prevents the temperature runaway phenomenon possibly caused by intense heat release during the reaction process through effective heat dissipation measures and temperature control strategies, and prevents the deactivation of the catalyst due to local hot spots.
[0016] (4) The present invention preferably uses water as the reaction solvent so that the generated ammonia can be quickly dissolved, which thermodynamically promotes the forward progress of the ammonia synthesis reaction and improves the efficiency of ammonia synthesis. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is the X-ray diffraction pattern of the catalyst prepared in Example 1. DETAILED DESCRIPTION
[0018] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0019] The first aspect of the present invention provides a method for preparing a nickel-based catalyst, the method comprising the following steps: (1) providing an alloy containing Ni, Al and an additive metal, wherein the additive metal is selected from at least one of Group VA metal elements, transition metal elements other than Group IVB and Group VB, and lanthanide metal elements; (2) grinding the alloy to obtain alloy powder; (3) subjecting the alloy powder to dealuminizing treatment in the presence of an alkali solution; (4) Aging the product obtained by the dealumination treatment in step (3) and the catalyst support in the presence of a solvent.
[0020] In the present invention, step (1) uses non-precious metal Ni as the main active component of the catalyst, successfully replacing the traditional low-pressure ammonia synthesis Ru metal, and provides a direction for the development of low-cost ammonia synthesis catalyst.
[0021] In the present invention, the source of the alloy containing Ni, Al and the auxiliary metal is not particularly limited, and the alloy can be purchased commercially or prepared by itself. Specifically, the alloy can be smelted by melting nickel particles, aluminum particles and the auxiliary metal according to a mass ratio. The smelting can be carried out in an arc melting furnace.
[0022] In the present invention, the auxiliary metal is selected from at least one of the group VA metal elements, transition metal elements except for group IVB and VB, and lanthanide metal elements. The group VA metal elements may be Sb, Bi, the transition metal elements except for group IVB and VB may be Mo, Mn, Re, Fe, Ru, Co, Pt, Cu, Ag, Au, Cd, and the lanthanide metal elements may be La, Ce.
[0023] According to the present invention, preferably, the auxiliary metal is selected from at least one of Co, Cu, Ag, Ru, Mo, Re, La, Sb and Bi, preferably Ru, Mo, Re, La, Sb, Bi, Ag, and more preferably Ru and / or Mo. The use of the aforementioned preferred auxiliary metals Ru and Mo is more conducive to forming a stable alloy structure with the active component nickel, thereby improving the stability of the catalyst.
[0024] According to the present invention, preferably, the additive metal content accounts for 0.1-5wt% of the Ni metal content, and more preferably 1-3wt%.
[0025] In the present invention, when the content of the auxiliary metal accounts for the Ni metal content within the above range, it is more conducive to maintaining the stability of the catalyst while the active sites of the nickel are not covered.
[0026] According to the present invention, preferably, in step (1), the mass ratio of Ni to Al is 1:1-3, more preferably 1:1-2.
[0027] In the present invention, when the mass ratio of Ni to Al satisfies the above range, it is more conducive to forming a good nickel skeleton structure.
[0028] In the present invention, there is no particular limitation on the alloy grinding method. Preferably, the alloy powder can be put into a planetary ball mill for grinding and sieving. The grinding time is preferably 10-40 minutes.
[0029] According to the present invention, preferably, in step (2), the alloy is ground to a size below 200 mesh.
[0030] In the present invention, when the alloy grinding size meets the above range, more active sites can be provided for the reaction raw materials.
[0031] According to the present invention, preferably, the conditions for the dealumination treatment in step (3) include: a temperature of 10-30° C. and a time of 2-5 h.
[0032] In the present invention, if the dealumination treatment temperature is too high, the catalyst will become porous and the thermal stability will be reduced.
[0033] In the present invention, in step (3), in the presence of alkaline solution, aluminum can be removed by reaction with alkali, and after aluminum is leached, Raney nickel with micropores of different sizes is left. The porous structure of the surface of Raney nickel makes it have high catalytic activity.
[0034] In the present invention, the dealumination treatment can be performed in a water bath.
[0035] In the present invention, there is no specific limitation on the alkali solution, as long as it can achieve the dealumination effect.
[0036] According to the present invention, preferably, the alkali in the alkali solution in step (3) is sodium hydroxide and / or potassium hydroxide.
[0037] According to the present invention, preferably, the concentration of the alkali solution in step (3) is 5-15 mol / L; According to the present invention, preferably, the amount of the alkali solution relative to Al is 5-10 mL / g 铝 .
[0038] In the present invention, when the amount of alkali solution meets the above range, it is more conducive to reducing the amount of alkali while ensuring the formation of a good skeleton structure, thereby reducing the processing cost.
[0039] According to a preferred embodiment of the present invention, the method further comprises, before step (4), washing the product obtained by the dealumination treatment in step (3). There is no particular limitation on the washing agent used for the washing, and it may be water, for example. The washing may be carried out according to conventional means in the art, and the washing may be carried out multiple times.
[0040] According to the present invention, preferably, the catalyst carrier in step (4) is selected from at least one of Al2O3, MgO, TiO2 and ZrO2.
[0041] In one specific embodiment of the present invention, TiO2 is preferably P25.
[0042] In the present invention, there is no specific limitation on the sources of the catalyst supports Al2O3, MgO, P25 and ZrO2, and they can be purchased from the market.
[0043] In the present invention, the solvent in step (4) is water, and there is no limitation on the amount of water used, as long as the alloy powder can be fully dispersed.
[0044] According to the present invention, preferably, the mass ratio of the catalyst carrier in step (4) to the Ni in the alloy in step (1) is 1-6:1, preferably 1-4:1.
[0045] In the present invention, when the mass ratio of the catalyst carrier to the Ni in the alloy of step (1) satisfies the above range, it is more conducive to increasing the active site density of nickel while maintaining a high dispersion of nickel particles.
[0046] According to the present invention, preferably, the aging conditions in step (4) include: a temperature of 50-100°C, preferably 60-90°C, and a time of 4-24 h, preferably 6-12 h.
[0047] According to the present invention, preferably, the method of step (4) further comprises adjusting the pH of the mixture containing the solvent, the product obtained by the dealumination treatment in step (3) and the catalyst carrier to 8-11 before aging, more preferably to 8-9. In the present invention, when the aging conditions meet the above range, it is more conducive to enhancing the coupling strength between the metal and the carrier.
[0048] By adopting the scheme of the present invention, the alloy is ground to less than 200 meshes, then dealumination is carried out, and finally a carrier is introduced for aging, so that the product obtained by dealumination treatment can be better combined with the catalyst carrier, which is more conducive to realizing the synthesis of ammonia under mild conditions.
[0049] In a specific embodiment of the present invention, preferably, concentrated aqueous ammonia is used to adjust the pH of the mixture of the product obtained by dealumination treatment and the catalyst support.
[0050] According to the present invention, preferably, the method further comprises filtering the product obtained by aging in step (4), and then washing the obtained solid product. The filtering and washing can be performed according to conventional techniques in the art.
[0051] According to the present invention, preferably, the obtained solid product (catalyst) is stored in water. Storing the catalyst in water is more conducive to preventing the catalyst from being oxidized by air and maintaining the high activity of the catalyst. In this preferred manner, the ammonia synthesis process is also carried out in the presence of water, which can make the catalyst preparation and application more economical and simple.
[0052] The second aspect of the present invention provides a nickel-based catalyst prepared by the preparation method of the first aspect.
[0053] The third aspect of the present invention provides use of the nickel-based catalyst of the second aspect in synthesizing ammonia.
[0054] A fourth aspect of the present invention provides a method for synthesizing ammonia, comprising: contacting nitrogen and hydrogen under ammonia synthesis conditions in the presence of a nickel-based catalyst and a solvent; wherein the nickel-based catalyst is the nickel-based catalyst described in the second aspect above.
[0055] According to the present invention, preferably, the solvent is water.
[0056] In the present invention, water is preferably used as the reaction solvent, which can dissolve the generated ammonia quickly, promote the forward progress of the ammonia synthesis reaction from a thermodynamic point of view, and improve the efficiency of ammonia synthesis.
[0057] In the present invention, the volume ratio of nitrogen to hydrogen is preferably 1:3.
[0058] In the present invention, there is no particular limitation on the amount of nitrogen and hydrogen used, as long as the pressure in the reactor satisfies the purpose of the present invention.
[0059] According to the present invention, preferably, the synthetic ammonia conditions include: temperature of 120-180°C, time of 2-6h, and pressure of 2-4MPa.
[0060] The catalyst provided by the present invention realizes efficient catalytic synthesis of ammonia at low temperature and low pressure, solves the problem that the traditional synthesis of ammonia reaction conditions are too harsh, greatly reduces the energy consumption and equipment requirements required for the reaction, and provides a more economical, efficient and safe solution for the synthesis of ammonia industry.
[0061] According to the present invention, preferably, the mass ratio of the nickel-based catalyst to the solvent is 1:4-8, preferably 1:5-8, wherein the nickel-based catalyst is calculated as nickel.
[0062] In the present invention, when the amount of the nickel-based catalyst meets the above range, it is more conducive to achieving efficient reaction and product selectivity while reducing costs.
[0063] The present invention has no particular limitation on the reaction device for synthesizing ammonia, which can be carried out in a high-pressure reactor or a fully mixed flow reactor. Preferably, the contact reaction is carried out in a tubular fully mixed flow reactor or a rotating bed fully mixed flow reactor. The inventors of the present invention have found in the course of research that the synthetic ammonia reaction carried out in a fully mixed flow reactor can prevent the temperature runaway phenomenon that may be caused by intense heat release during the reaction process and prevent the deactivation of the catalyst due to local hot spots through effective heat dissipation measures and temperature control strategies.
[0064] In the present invention, preferably, the stirring speed of the fully mixed flow reactor is 150-1000 rpm, preferably 300-600 rpm.
[0065] In the present invention, there is no particular limitation on the heating rate of the fully mixed flow reactor, and preferably the heating rate is 1-3°C / min.
[0066] The present invention will be described in detail below through examples.
[0067] The ammonia content in the products of the examples and comparative examples was analyzed by indophenol blue spectrophotometry.
[0068] A 50 mL fully mixed flow reactor was used in the examples and comparative examples.
[0069] Example 1 Preparation of nickel-based catalysts: (1) Weigh 50 g of nickel particles, 50 g of aluminum particles and 1 g of molybdenum powder and melt them in an arc melting furnace; (2) Grind the alloy in a planetary ball mill for 30 minutes and sieve to a powder of <200 mesh; (3) Treat the alloy powder with 500 mL of 10 mol / L KOH solution in a 10°C water bath for 2 h to leach Al; (4) The alloy powder was washed 15 times with water and dispersed in water. 100 g of Al2O3 powder was added. The pH was adjusted to 8 with concentrated ammonia water and aged at 80°C for 6 h. After filtration, a highly active NiMo / Al2O3 catalyst was obtained and the catalyst was stored in water.
[0070] Test of catalyst performance for ammonia synthesis: A wet catalyst containing 5 g of metallic nickel was added to the fully mixed flow reactor, and the total content of the solvent water was adjusted to 20 g. After the reactor was sealed, a mixed gas with a volume ratio of N2:H2=1:3 was introduced to replace the residual air three times. After the pressure was set to 3 MPa, the reactor was heated to 150°C at a rate of 2°C / min and reacted at a speed of 600 rpm for 3 hours. After the reaction was completed, the ammonia content in the product was analyzed by indigo blue spectrophotometry, and the results are listed in Table 1.
[0071] Figure 1 is the X-ray diffraction pattern of the prepared catalyst. Figure 1 It can be seen that the Raney nickel particles are successfully loaded on the alumina carrier.
[0072] Example 2 Preparation of nickel-based catalysts: (1) Weigh 50 g of nickel pellets, 100 g of aluminum pellets and 0.5 g of ruthenium powder and smelt them in an arc melting furnace; (2) Grind the alloy in a planetary ball mill for 30 minutes and sieve to a powder of <200 mesh; (3) Treat the alloy powder with 500 mL of 15 mol / L NaOH solution in a 30°C water bath for 5 hours to leach Al; (4) The alloy powder was washed 15 times with water and dispersed in water. 50 g of P25 powder was added. The pH was adjusted to 9 with concentrated ammonia water and aged at 60 °C for 10 h. After filtering and washing, a highly active NiRu / TiO2 catalyst was obtained and the catalyst was stored in water.
[0073] Test of catalyst performance for ammonia synthesis: A wet catalyst containing 5g of metallic nickel was added to the fully mixed flow reactor, and the content of solvent water was adjusted to 20g. After the reactor was sealed, a mixed gas with a volume ratio of N2:H2=1:3 was introduced to replace the residual air three times. After the pressure was set to 2MPa, the reactor was heated to 120°C at a rate of 1°C / min and reacted at a speed of 300rpm for 2 hours. After the reaction was completed, the ammonia content in the product was analyzed by indigo blue spectrophotometry, and the results are listed in Table 1.
[0074] Example 3 Preparation of nickel-based catalysts: (1) Weigh 50 g of nickel particles, 75 g of aluminum particles and 1.5 g of molybdenum powder and melt them in an arc melting furnace; (2) Grind the alloy in a planetary ball mill for 20 minutes and sieve to a powder of <200 mesh; (3) Treat the alloy powder with 600 mL of 5 mol / L KOH solution in a 20°C water bath for 5 hours to leach Al; (4) The alloy powder was washed 15 times with water and dispersed in water. 200 g of ZrO2 powder was added. The pH was adjusted to 8.5 with concentrated ammonia water and aged at 90 °C for 12 h. After filtering and washing, a highly active NiMo / ZrO2 catalyst was obtained and the catalyst was stored in water.
[0075] Test of catalyst performance for ammonia synthesis: A wet catalyst containing 5g of metallic nickel was added to the fully mixed flow reactor, and the content of solvent water was adjusted to 20g. After the reactor was sealed, a mixed gas with a volume ratio of N2:H2=1:3 was introduced to replace the residual air three times. After the pressure was set to 2MPa, the reactor was heated to 180°C at a rate of 3°C / min and reacted at a speed of 400rpm for 3 hours. After the reaction was completed, the ammonia content in the product was analyzed by indigo blue spectrophotometry, and the results are listed in Table 1.
[0076] Example 4 Preparation of nickel-based catalysts: (1) Weigh 50 g of nickel particles, 50 g of aluminum particles and 1 g of lanthanum powder and smelt them in an arc melting furnace; (2) Grind the alloy in a planetary ball mill for 20 minutes and sieve to a powder of <200 mesh; (3) Treat the alloy powder with 500 mL of 10 mol / L KOH solution in a 10°C water bath for 4 hours to leach Al; (4) The alloy powder was washed 15 times with water and dispersed in water. 100 g of Al2O3 powder was added. The pH was adjusted to 8 with concentrated ammonia water and aged at 80°C for 6 h. After filtering and washing, a highly active NiLa / Al2O3 catalyst was obtained and the catalyst was stored in water.
[0077] Test of catalyst performance for ammonia synthesis: A wet catalyst containing 5g of metallic nickel was added to the fully mixed flow reactor, and the content of solvent water was adjusted to 20g. After the reactor was sealed, a mixed gas with a volume ratio of N2:H2=1:3 was introduced to replace the residual air three times. After the pressure was set to 3MPa, the reactor was heated to 150°C at a rate of 2°C / min and reacted at a speed of 600rpm for 6 hours. After the reaction was completed, the ammonia content in the product was analyzed by indigo blue spectrophotometry, and the results are listed in Table 1.
[0078] Example 5 Preparation of nickel-based catalysts: (1) Weigh 50 g of nickel particles, 200 g of aluminum particles and 1 g of molybdenum powder and smelt them in an arc melting furnace; (2) Grind the alloy in a planetary ball mill for 10 minutes and sieve to a powder of <200 mesh; (3) Treat the alloy powder with 1000 mL of 10 mol / L KOH solution in a 10°C water bath for 2 h to leach Al. (4) The alloy powder was washed 15 times with water and dispersed in water. 100 g of Al2O3 powder was added. The pH was adjusted to 8 with concentrated ammonia water and aged at 80°C for 8 h. After filtering and washing, a highly active NiMo / Al2O3 catalyst was obtained and the catalyst was stored in water.
[0079] Test of catalyst performance for ammonia synthesis: A wet catalyst containing 5g of metallic nickel was added to the fully mixed flow reactor, and the content of solvent water was adjusted to 20g. After the reactor was sealed, a mixed gas with a volume ratio of N2:H2=1:3 was introduced to replace the residual air three times. After the pressure was set to 3MPa, the reactor was heated to 140°C at a rate of 2°C / min and reacted at a speed of 600rpm for 3 hours. After the reaction was completed, the ammonia content in the product was analyzed by indigo blue spectrophotometry, and the results are listed in Table 1.
[0080] Example 6 (1) Weigh 50 g of nickel particles, 50 g of aluminum particles and 0.3 g of molybdenum powder and melt them in an arc melting furnace; (2) Grind the alloy in a planetary ball mill for 20 minutes and sieve to a powder of <200 mesh; (3) Treat the alloy powder with 400 mL of 10 mol / L KOH solution in a 20°C water bath for 4 hours to leach Al; (4) The alloy powder was washed 15 times with water and dispersed in water. 100 g of ZrO2 powder was added. The pH was adjusted to 8.5 with concentrated ammonia water and aged at 80°C for 10 h. After filtering and washing, a highly active NiMo / ZrO2 catalyst was obtained and the catalyst was stored in water.
[0081] Test of catalyst performance for ammonia synthesis: A wet catalyst containing 5g of metallic nickel was added to the fully mixed flow reactor, and the content of solvent water was adjusted to 20g. After the reactor was sealed, a mixed gas with a volume ratio of N2:H2=1:3 was introduced to replace the residual air three times. After the pressure was set to 2MPa, the reactor was heated to 150°C at a rate of 3°C / min and reacted at a speed of 600rpm for 3 hours. After the reaction was completed, the ammonia content in the product was analyzed by indigo blue spectrophotometry, and the results are listed in Table 1.
[0082] Example 7 (1) Weigh 50 g of nickel pellets, 100 g of aluminum pellets and 0.5 g of ruthenium powder and smelt them in an arc melting furnace; (2) Grind the alloy in a planetary ball mill for 30 minutes and sieve to a powder of <200 mesh; (3) Treat the alloy powder with 600 mL of 15 mol / L NaOH solution in a 50°C water bath for 3 hours to leach Al; (4) The alloy powder was washed 15 times with water and dispersed in water. 100 g of P25 powder was added. The pH was adjusted to 9 with concentrated ammonia water and aged at 80 °C for 10 h. After filtering and washing, a highly active NiRu / TiO2 catalyst was obtained and the catalyst was stored in water.
[0083] Test of catalyst performance for ammonia synthesis: A wet catalyst containing 5g of metallic nickel was added to the fully mixed flow reactor, and the content of solvent water was adjusted to 20g. After the reactor was sealed, a mixed gas with a volume ratio of N2:H2=1:3 was introduced to replace the residual air three times. After the pressure was set to 4MPa, the reactor was heated to 150°C at a rate of 3°C / min and reacted at a speed of 600rpm for 3 hours. After the reaction was completed, the ammonia content in the product was analyzed by indigo blue spectrophotometry, and the results are listed in Table 1.
[0084] Example 8 (1) Weigh 50 g of nickel pellets, 100 g of aluminum pellets and 0.5 g of ruthenium powder and smelt them in an arc melting furnace; (2) Grind the alloy in a planetary ball mill for 30 minutes and sieve to a powder of <200 mesh; (3) Treat the alloy powder with 500 mL of 10 mol / L KOH solution in a 30°C water bath for 3 hours to leach Al; (4) The alloy powder was washed 15 times with water and dispersed in water. 25 g of Al2O3 powder was added. The pH was adjusted to 8.5 with concentrated ammonia water and aged at 80°C for 10 h. After filtering and washing, a highly active NiRu / Al2O3 catalyst was obtained and the catalyst was stored in water.
[0085] Test of catalyst performance for ammonia synthesis: A wet catalyst containing 5g of metallic nickel was added to the fully mixed flow reactor, and the content of solvent water was adjusted to 20g. After the reactor was sealed, a mixed gas with a volume ratio of N2:H2=1:3 was introduced to replace the residual air three times. After the pressure was set to 4MPa, the reactor was heated to 150°C at a rate of 2°C / min and reacted at a speed of 600rpm for 3 hours. After the reaction was completed, the ammonia content in the product was analyzed by indigo blue spectrophotometry, and the results are listed in Table 1.
[0086] Example 9 (1) Weigh 50 g of nickel particles, 75 g of aluminum particles and 1.5 g of molybdenum powder and melt them in an arc melting furnace; (2) Grind the alloy in a planetary ball mill for 30 minutes and sieve to a powder of <200 mesh; (3) Treat the alloy powder with 750 mL of 10 mol / L KOH solution in a 20°C water bath for 5 hours to leach Al. (4) The alloy powder was washed 15 times with water and dispersed in water. 150 g of ZrO2 powder was added. The pH was adjusted to 8.5 with concentrated ammonia water and aged at 40°C for 12 h. After filtering and washing, a highly active NiMo / ZrO2 catalyst was obtained and the catalyst was stored in water.
[0087] Test of catalyst performance for ammonia synthesis: A wet catalyst containing 5g of metallic nickel was added to the fully mixed flow reactor, and the content of solvent water was adjusted to 20g. After the reactor was sealed, a mixed gas with a volume ratio of N2:H2=1:3 was introduced to replace the residual air three times. After the pressure was set to 3MPa, the reactor was heated to 160°C at a rate of 2°C / min and reacted at a speed of 600rpm for 4 hours. After the reaction was completed, the ammonia content in the product was analyzed by indigo blue spectrophotometry, and the results are listed in Table 1.
[0088] Example 10 (1) Weigh 50 g of nickel pellets, 100 g of aluminum pellets and 0.5 g of ruthenium powder and smelt them in an arc melting furnace; (2) Grind the alloy in a planetary ball mill for 20 minutes and sieve to a powder of <200 mesh; (3) Treat the alloy powder with 750 mL of 10 mol / L KOH solution in a 30°C water bath for 2 hours to leach Al. (4) The alloy powder was washed 15 times with water and dispersed in water. 50 g of P25 powder was added. The pH was adjusted to 7 with concentrated ammonia water and aged at 70 °C for 10 h. After filtering and washing, a highly active NiRu / TiO2 catalyst was obtained and the catalyst was stored in water.
[0089] Test of catalyst performance for ammonia synthesis: A wet catalyst containing 5g of metallic nickel was added to the fully mixed flow reactor, and the content of solvent water was adjusted to 20g. After the reactor was sealed, a mixed gas with a volume ratio of N2:H2=1:3 was introduced to replace the residual air three times. After the pressure was set to 2MPa, the reactor was heated to 160°C at a rate of 3°C / min and reacted at a speed of 600rpm for 5 hours. After the reaction was completed, the ammonia content in the product was analyzed by indigo blue spectrophotometry, and the results are listed in Table 1.
[0090] Comparative Example 1 (1) Weigh 50 g of nickel particles, 50 g of aluminum particles and 1 g of molybdenum powder and melt them in an arc melting furnace; (2) Grinding the alloy precursor in a planetary ball mill for 30 minutes and sieving to a powder of <200 mesh; (3) Treat the alloy powder with 500 mL of 10 mol / L KOH solution in a 10°C water bath for 5 hours to leach Al; (4) The alloy powder was washed 15 times with water and dispersed in water for storage.
[0091] The catalyst's ammonia synthesis performance was tested in the same manner as in Example 1. The results are listed in Table 1.
[0092] Comparative Example 2 According to the actual nickel content and ruthenium content of the catalyst in Example 2, mixed salt solutions of nickel nitrate and ruthenium trichloride were prepared respectively, 50 g of P25 powder was added to the mixed salt solution, and the pH was adjusted to 9 with concentrated ammonia water under stirring, and aged at 60°C for 10 h. After filtration, washing and drying, a NiRu / TiO2 catalyst was obtained. The catalyst containing 5 g of nickel was loaded into a tubular furnace, the reaction temperature was set to 350°C, and hydrogen was introduced at a flow rate of 20 mL / min for reduction under normal pressure for 4 hours. After cooling to room temperature, the catalyst was placed in 20 g of water for storage.
[0093] The catalyst's ammonia synthesis performance was tested in the same manner as in Example 2. The results are listed in Table 1.
[0094] The test results of the catalyst synthesis ammonia performance in the embodiments and comparative examples are shown in Table 1.
[0095] Table 1
[0096] The ICP test results of the ammonia synthesis reaction solutions of the embodiments and comparative examples are shown in Table 2.
[0097] Table 2
[0098] Combining Table 1 and Table 2, it can be seen that the catalyst method provided by the present invention can break the kinetic limitations of ammonia synthesis under low temperature and low pressure, so that ammonia synthesis can occur under relatively mild conditions. The application method of the ammonia synthesis catalyst provided by the present invention adopts a fully mixed flow reaction mode with water as the reaction solvent, which not only effectively avoids the temperature rise caused by the violent exothermic reaction, but also utilizes the strong solubility of ammonia in water to enable the generated ammonia to dissolve quickly, which thermodynamically promotes the forward progress of the ammonia synthesis reaction and improves the efficiency of ammonia synthesis. When non-precious metal nickel is used as the active component, the ammonia synthesis rate reached 1.46μmol·g -1 ·h -1 The catalyst of the present invention has a simple and easy preparation process, mild conditions, low raw material cost, and is suitable for large-scale production and industrial application. When the unloaded NiMo catalyst is used in Comparative Example 1, the ammonia yield is only 0.05 μmol·g -1 ·h -1 , from the results of elemental analysis of the reaction solution, a large amount of metal was lost (Table 2). The catalyst prepared by direct precipitation method in Comparative Example 2 cannot provide nickel active sites, and its catalytic activity is much lower than the results of other examples in the present invention, which shows that the method described in the present invention can produce a highly active skeleton Ni structure, so that the active site density of Ni is greatly improved.
[0099] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a nickel-based catalyst, characterized in that: The method comprises the following steps: (1) providing an alloy containing Ni, Al and an additive metal, wherein the additive metal is selected from at least one of Group VA metal elements, transition metal elements other than Group IVB and Group VB, and lanthanide metal elements; (2) grinding the alloy to obtain alloy powder; (3) subjecting the alloy powder to dealuminizing treatment in the presence of an alkali solution; (4) Aging the product obtained by the dealumination treatment in step (3) and the catalyst support in the presence of a solvent.
2. The method according to claim 1, wherein: The auxiliary metal is selected from at least one of Co, Cu, Ag, Ru, Mo, Re, La, Sb and Bi, preferably Ru, Mo, Re, La, Sb, Bi, Ag, more preferably Ru and / or Mo; and / or, the additive metal content accounts for 0.1-5wt% of the Ni metal content, preferably 1-3wt%; And / or, in step (1), the mass ratio of Ni to Al is 1:1-3, preferably 1:1-2.
3. The method according to claim 1 or 2, wherein: Step (2) grinding the alloy to a size below 200 mesh.
4. The method according to any one of claims 1 to 3, wherein: The conditions of the dealumination treatment in step (3) include: temperature of 10-30°C and time of 2-5 h; Preferably, the alkali in the alkali solution in step (3) is sodium hydroxide and / or potassium hydroxide; Preferably, the concentration of the alkali solution in step (3) is 5-15 mol / L; Preferably, the amount of alkali solution relative to Al is 5-10 mL / g 铝 .
5. The method according to any one of claims 1 to 4, wherein: The catalyst carrier is selected from at least one of Al2O3, MgO, TiO2 and ZrO2; Preferably, the mass ratio of the catalyst carrier to Ni in the alloy of step (1) is 1-6:1, preferably 1-4:
1.
6. The method according to any one of claims 1 to 5, wherein: The aging conditions include: a temperature of 50-100°C, preferably 60-90°C, and a time of 4-24 h, preferably 6-12 h; Preferably, the aging is carried out at a pH of 8-11, preferably at a pH of 8-9.
7. A nickel-based catalyst obtained by the preparation method according to any one of claims 1 to 6.
8. Use of the nickel-based catalyst according to claim 7 in synthesizing ammonia.
9. A method for synthesizing ammonia, characterized in that: The method includes: Under ammonia synthesis conditions, in the presence of a nickel-based catalyst and a solvent, nitrogen and hydrogen are contacted and reacted; wherein the nickel-based catalyst is the nickel-based catalyst according to claim 7; Preferably, the synthetic ammonia conditions include: temperature of 120-180°C, time of 2-6h, and pressure of 2-4MPa; Preferably, the mass ratio of the nickel-based catalyst to the solvent is 1:4-8; the nickel-based catalyst is calculated in terms of nickel; Preferably, the solvent is water.
10. The method according to claim 9, wherein: The contact reaction is carried out in a fully mixed flow reactor; Preferably, the stirring speed of the fully mixed flow reactor is 150-1000 rpm.
Citation Information
Patent Citations
Preparation of an ammonia synthesis catalyst and ammonia synthesis system and method
CN114471552B
Synthetic ammonia catalyst as well as preparation method and application thereof
CN117920204A